Ocular Manifestations of Diabetes Mellitus: It’s Remedies and Prevention - Bhattarai, Sanjeev; Adhikari, Pragati Gautam; Kumar Sah, Deependra (Medical Journal of Eastern Nepal, 2023)
Diabetes mellitus which is a multi systemic disease is a common public health problem which can affect children, young people, adults and older people due to uncontrolled hyperglycemia. Ocular and other systemic complications of diabetes are becoming the most significant cause of visual impairment and other morbidities and are either preventable or curable with early detection and prompt treatment. Its prevalence is increasing globally with sight threatening ocular manifestations. The most of the published articles highlighted that the common ocular manifestations were diabetic retinopathy, snow flake cataract, primary open angle glaucoma, corneal lesions, recurrent stye, Chalazion and extraocular muscle palsies. Treatment options for diabetic retinopathy are laser photocoagulation and intravitreal injection of steroids. Expert opinion is always required in a case with glaucoma, cataract, optic nerve disorders and cranial nerve palsies. Control of blood sugar level, proper nutrition and adequate physical exercise and periodic eye examination can play a crucial role for its prevention.